Knowledge and practice of breastfeeding among mothers in Arma’a District Shabwah Governorate - Yemen - Omer Maroof, Mofareg Hasan; Faiz Daud,; Natrah Rani, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Introduction Breastfeeding is almost universal, but there are many barriers for proper breast feeding practices. Inadequate knowledge, or inappropriate practice, of breastfeeding may lead to undesirable consequences. The aim of this study was to assess breastfeeding knowledge, and practice among mothers in Arma’a district Shabwah governorate and identify factors that may affect breastfeeding practice in the study population. Methods A cross-sectional study using pre-tested validated structured questionnaire conducted among mothers who were attending Arma’a hospital and four health care units around Arma'a district. Sample size was 130 mothers who had at least one child aged two years or younger. Breastfeeding knowledge and practice of participants were assessed based on their experience with the last child. Results This study found that there are only 24 mothers (18.6%) have good knowledge while 106 mothers (81.4%) have low knowledge. 63 mothers (48.5%) had good breastfeeding practice while 67 mothers (51.5%) have poor breastfeeding practice. 54.0% mothers that have good knowledge have good practice while 52.8% mothers of poor knowledge have poor practice. Mothers’s knowledge was significantly associated with their education level and their practice was significantly associated with the number of pregnancies (p-value=0.04 and =0.027 respectively). There was no significant association with other demographic data, and between knowledge and practice. No exclusive breastfeeding reported in this study. Conclusions This study shows that undesirable cultural practices such as giving pre-lacteal, avoiding exclusive breastfeeding are still prevalent among the mothers. The maternal knowledge towards breastfeeding was very low and there was big gap between actual and desired practices.